Evaluation of nasal proportions in adults with class I and class II skeletal patterns: A cephalometric study - Vinay V Umale; Kamlesh Singh; Aftab Azam; Madhvi Bhardwaj; Rohit Kulshrestha (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study was to evaluate sexual dimorphism in nasal proportions of Class I and Class II skeletal malocclusions in adults. Materials And Methods: The sample comprised 120 patients (females 18 years and above and males 21 years and above), with no history of previous orthodontic treatment or functional jaw orthopedic treatment. They were divided into different groups based on point A-Nasion-point B (ANB) angle and gender. Groups I and II included 30 males and 30 females with skeletal class I malocclusion (ANB 0-4 degrees). Groups III and IV included 30 males and 30 females with skeletal class II malocclusion, respectively (ANB above 4 degrees). Results: In regards to the comparison between males and females (Class I + Class II), nasal length (P < 0.001), nasal depth 1 (P < 0.001), nasal depth 2 (P < 0.001), nasobasal angle (P < 0.001), soft tissue convexity angle (P < 0.001), and nasal bone length (P < 0.008) were found to be statistically significant. Nasobasal angle was found to be significantly higher in females than in males (Class I) (P < 0.001). Nasolabial angle was prominent in class I males than in class I females (P < 0.001). Soft tissue convexity angle of Class I participants was significantly lower than that of Class II participants (P < 0.001), whereas nasobasal angle and nasomental angle of Class I participants were found to be significantly higher than that of Class II participants (P < 0.001). Conclusion: Sexual dimorphism was found in various nasal parameters. Significant amount of differences was found in the nasal proportions of Class I and Class II (male and female) participants.